PRAGMATIKA BAHASA, PRINSIP PENGGUNAAN BAHASA, DAN KESANTUNAN BERBAHASA - Al Amin; Seihk Imam Al Asary; Silvina Noviyanti (STKIP Subang, 2025)
This article examines the relationship between pragmatics, principles of language use, and politeness in communication. Using a literature review method, the study explores how pragmatic elements such as context, implicature, and speech acts interact with conversational principles and politeness strategies. The findings show that pragmatic competence helps speakers interpret implied meanings, apply conversational maxims, and use polite strategies in various social situations. The discussion highlights that pragmatic awareness strengthens communicative accuracy, principles of language use guide effective exchanges, and politeness supports social harmony. The study concludes that integrating these three components is essential for producing effective and respectful communication.